2022
DOI: 10.1002/ejhf.2513
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue related to left atrial and ventricular function in heart failure with preserved versus reduced and mildly reduced ejection fraction

Abstract: Aim Different associations between epicardial adipose tissue (EAT) and cardiac function have been suggested in patients with heart failure with preserved (HFpEF) versus reduced and mildly reduced ejection fraction (HFrEF/HFmrEF). However, few studies have directly compared the association between EAT and left atrial (LA) and left ventricular (LV) function in patients with HFpEF and HFrEF/HFmrEF. Methods and results We studied EAT thickness using transthoracic echocardiography in a multicentre cohort of 149 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Our analysis focuses on LA reservoir strain(LAs-s), LACI, and LVGLS as the key parameters of left cardiac function, considering their predictive abilities for LA dysfunction and LV dysfunction, respectively [19]. After multivariate adjustment, simple obesity substantially worsens overall left cardiac function(including LAs-s, LACI, and LV GLS) compared with non-obese individuals(p 0.05, Figure 1).…”
Section: Association Between Obesity Metabolic Health and Left Cardia...mentioning
confidence: 99%
“…Our analysis focuses on LA reservoir strain(LAs-s), LACI, and LVGLS as the key parameters of left cardiac function, considering their predictive abilities for LA dysfunction and LV dysfunction, respectively [19]. After multivariate adjustment, simple obesity substantially worsens overall left cardiac function(including LAs-s, LACI, and LV GLS) compared with non-obese individuals(p 0.05, Figure 1).…”
Section: Association Between Obesity Metabolic Health and Left Cardia...mentioning
confidence: 99%
“…However, some longitudinal studies have shown that higher EAT at baseline is associated with new‐onset HFpEF, 6,30 as well as a worse prognosis in those with established HFpEF, 7 independent of overall obesity and important comorbidities. An overview of the recent studies that investigated EAT in relation to HFpEF is shown in Table 1 6,7,23,25–27,30–41 . Of note, one study by Haykowsky et al 32 .…”
Section: Epicardial Adipose Tissue and Hfpefmentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) may have a different prognostic impact in patients with HF according to their left ventricular ejection fraction (LVEF) 4 . Jin et al 5 . studied the thickness of EAT using transthoracic echocardiography in 99 patients with HFpEF, 366 patients with HF with reduced (HFrEF) or mildly reduced ejection fraction (HFmrEF) and 149 controls without HF.…”
Section: Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%